TANTANGAN PENDIDlKAN DALAM RANGKA PELAKSANAAN OTONOMI DAERAH - Heru Pratomo (Jurnal Cakrawala Pendidikan, 2002)
Started from the year 2001, regional autonomy is implemented and S9 autonomy in education. In order to implement  autonomy in education, every educational institution is expected to be able to develop income generating activities to cover its operational cost. An advanced education in a district could have a role as income generating resources for that district, for it could draw money from other district. It also generates taxes from boarding houses. To cope with the implementation of autonomy, educational institution should refonn itself, not to mention that education should be managed professionally. Refonn in education not  only cover the whole component ofeducation process, those are : input, curriculum and teaching-learning process, infrastructure, and academic staff, but also the placement of the graduate. The conclusions are: (I) in order to implement the autonomy, education should be managed profesionally since education is not only investment but also c6mmdity, and (2) refonn in education should cover the whole component ofeducation system.